A catalyst component for olefin polymerization, a catalyst system, and a preparation method and application thereof

CN118812754BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310429371.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-20
Publication Date
2026-10-13
Estimated Expiration
2043-04-20

AI Technical Summary

Technical Problem

由于这类催化剂的形态和粒径分布通过溶液的结晶析出过程控制,制备过程中影响因素多,因而催化剂的颗粒形态往往不易控制

Benefits of technology

[0075]本发明采用(甲基)丙烯酸酯/α-烯烃共聚物作为表面活性剂,所制备球形催化剂组分粒形完好且性能优良,用于丙烯聚合时,具有较高的聚合活性和氢调敏感性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812754B_ABST
    Figure CN118812754B_ABST
Patent Text Reader

Abstract

The application provides a catalyst component for olefin polymerization, a catalyst system and a preparation method and application thereof, and belongs to the technical field of olefin polymerization.The catalyst component comprises the following components or reaction products of the following components: (1) a magnesium compound; (2) an organic epoxide compound; (3) an organic phosphorus compound; (4) a cocatalyst; (5) a titanium compound; (6) an internal electron donor compound; and (7) a surfactant; the surfactant comprises one or more selected from (meth)acrylate / alpha-olefin copolymers.The catalyst component prepared by the application has good sphericity, excellent catalyst performance, high polymerization activity and hydrogen sensitivity when used for propylene polymerization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of olefin polymerization technology, specifically relating to a catalyst component for olefin polymerization and its preparation method, a catalyst system containing the catalyst component and its application. Background Technology

[0002] Supported Ziegler-Natta catalysts have been widely developed due to the ability to control their morphology through the support, especially olefin polymerization catalysts supported on magnesium chloride. Preparing catalysts with favorable particulate morphology is beneficial for industrial plant operation and has always been a key aspect of catalyst development. Currently, various techniques exist for preparing olefin polymerization catalyst components with well-defined morphologies.

[0003] One approach involves first preparing a magnesium compound support, then reacting the support with a titanium compound to generate a titanium and magnesium-containing catalyst solid, on which an internal electron-donating compound is loaded to form the catalyst component. Commonly used industrial supports include magnesium chloride ethanol adduct and ethoxymagnesium. In this type of technology, the morphology and particle size distribution of the catalyst are determined by the pre-prepared magnesium compound support. Well-known techniques such as high-speed stirring, high-pressure extrusion, spraying, and high-gravity methods are all used to prepare such solids, which are typically spherical. However, these techniques are usually energy-intensive and complex, making continuous production of the catalyst component impossible.

[0004] Another method typically involves preparing a homogeneous solution containing magnesium compounds, then reacting it with a chlorinating agent to precipitate a solid titanium / magnesium complex, on which an internal electron-donating compound is loaded to form the catalyst component. A key feature of this method is that the support is no longer prepared separately during catalyst preparation; instead, the titanium / magnesium catalyst or catalyst intermediate is precipitated from the solution via co-crystallization. Because the morphology and particle size distribution of this type of catalyst are controlled through the crystallization process, many factors influence the preparation, making it difficult to control the catalyst particle morphology. Early published Chinese invention patents, such as CN85100997A and CN1097597C, precipitated particulate catalysts with wide particle size distributions and poor particle shape. In recent years, the preparation of spherical catalysts using emulsion molding technology has attracted increasing attention. Chinese invention patents such as CN103619475B, CN107207657A, and CN114426597A use emulsification technology to control the crystallization process, resulting in precipitated spherical solids, which has greatly improved the morphology. However, the activity and hydrogen sensitivity of the catalysts need to be further improved. Summary of the Invention

[0005] In view of the problems existing in the prior art, the present invention has explored through a large number of experiments and found that when (meth)acrylate / α-olefin copolymer is used as a surfactant, the olefin polymerization catalyst component prepared not only has good sphericity, but also excellent catalyst performance. The prepared spherical catalyst component has excellent performance and has high polymerization activity and hydrogen regulation sensitivity when used for propylene polymerization.

[0006] One of the objectives of this invention is to provide a spherical catalyst component for olefin polymerization, comprising the following components or reaction products of the following components: (1) magnesium compounds, (2) organic epoxy compounds, (3) organic phosphorus compounds, (4) precipitation aids, (5) titanium compounds, (6) internal electron donor compounds, and (7) surfactants.

[0007] The surfactants described in this invention include (meth)acrylate / α-olefin copolymers.

[0008] The (meth)acrylate / α-olefin copolymer of the present invention is obtained by copolymerizing one or more (meth)acrylates with one or more α-olefins.

[0009] Optionally, the content of α-olefin-derived structural units in the (meth)acrylate / α-olefin copolymer of the present invention is 10wt% to 90wt%, preferably 20wt% to 80wt%.

[0010] Optionally, according to the present invention, the number average molecular weight of the (meth)acrylate / α-olefin copolymer is 1,000 to 100,000.

[0011] Optionally, the (meth)acrylate monomer in the (meth)acrylate / α-olefin copolymer of the present invention is derived from the general formula: CH2=C(R a COO(R) b ) indicates that R a R is a hydrogen atom or a methyl group. b It is selected from straight-chain or branched alkyl groups with 1 to 30 carbon atoms, cycloalkyl groups with 3 to 30 carbon atoms, or aromatic groups with 6 to 30 carbon atoms.

[0012] Optionally, the (meth)acrylate monomers described in this invention may include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, and dodecyl (meth)acrylate.

[0013] In this invention, a single (meth)acrylate monomer can be used, or multiple (meth)acrylate monomers can be used in combination.

[0014] Optionally, the α-olefin monomer in the (meth)acrylate / α-olefin copolymer of the present invention is derived from the general formula: CH2=CHR c It indicates that R c It is selected from hydrogen atoms, straight-chain or branched alkyl groups with 1 to 30 carbon atoms, and cycloalkyl groups with 3 to 30 carbon atoms.

[0015] Optionally, the α-olefin monomers of the present invention may include, but are not limited to, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadene, 1-hexadecene, 1-heptadecene, 1-heptadecene, 1-octadecene, 1-nonadene, 1-eicosene, 1-ticosene, 1-ticosene, 3-methyl-1-butene, and 4-methyl-1-pentene.

[0016] In this invention, a single α-olefin monomer can be used, or multiple α-olefin monomers can be used in combination.

[0017] Optionally, the magnesium compound of the present invention has the general formula MgX2, wherein X is selected from bromine, chlorine or iodine. Specifically, the magnesium compound may be selected from at least one of magnesium dichloride, magnesium dibromide and magnesium diiodide, preferably magnesium dichloride.

[0018] Optionally, the organic epoxy compound of the present invention is selected from one or more of the oxidation products of aliphatic olefins and the oxidation products of halogenated aliphatic olefins, wherein the aliphatic olefins and halogenated aliphatic olefins independently have 2 to 8 carbon atoms. Specifically, the organic epoxy compound may be selected from one or more of ethylene oxide, propylene oxide, epichlorohydrin, epichlorohydrin, epichlorohydrin, butane oxide, butadiene dieoxide, butadiene dioxide, methyl glycidyl ether, and diglycidyl ether, preferably epichlorohydrin.

[0019] Optionally, the organophosphorus compound of the present invention is selected from one or more compounds shown in formula (1) and formula (2):

[0020]

[0021] In formulas (1) and (2), R1, R2, R3, R4, R5, and R6 are each independently selected from straight-chain or branched alkanes with 1 to 20 carbon atoms, cycloalkanes with 1 to 20 carbon atoms, haloalkanes with 1 to 20 carbon atoms, aromatic hydrocarbons with 1 to 20 carbon atoms, or aromatic hydrocarbons with substituents with 1 to 20 carbon atoms. Specifically, the organophosphorus compound is selected from one or more of trimethyl phosphate, triethyl phosphate, tributyl phosphate, tripentyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, and benzyl phosphite, preferably tributyl phosphate.

[0022] Optionally, the precipitation aid of the present invention is selected from one or more of organic acid anhydrides, organic acids, organic ketones, and organic ethers; specifically, the precipitation aid is selected from one or more of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic dianhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, dimethyl ether, diethyl ether, propyl ether, butyl ether, and pentyl ether, preferably phthalic anhydride.

[0023] Optionally, the titanium compound of the present invention, such as the structure TiX', m (OR d ) 4-m This indicates that X' is a halogen, and R... d It is a hydrocarbon group with 1 to 20 carbon atoms, and m is an integer from 1 to 4.

[0024] Optionally, the titanium compound is selected from at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxy, titanium tetraethoxy, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloromonoethoxy, preferably titanium tetrachloride.

[0025] Optionally, the internal electron-donating compound of the present invention is selected from one or more of esters, ethers, ketones, amines, and silanes; preferably, it is selected from one or more of mono- or poly-aliphatic carboxylic acid esters, aromatic carboxylic acid esters, diol esters, and diethers; more preferably, it is selected from one or more of di-aliphatic carboxylic acid esters, aromatic carboxylic acid esters, diol esters, and diethers; and even more preferably, it is selected from one or more of phthalates, malonates, succinates, glutarates, diol esters, and 1,3-diethers.

[0026] Optionally, the internal electron-donating compound is selected from at least one of di-n-butyl phthalate, diisobutyl phthalate, 2,4-pentanediol dibenzoate, 3,5-heptanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, diisobutyl 2,2-dimethylsuccinate, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-dimethoxymethylfluorene.

[0027] Optionally, according to the present invention, the spherical catalyst component further comprises an organic solvent; the organic solvent is an aromatic hydrocarbon compound, preferably one or more of toluene, ethylbenzene, benzene, and xylene.

[0028] Optionally, according to the present invention, per mole of magnesium compound, the amount of organic epoxy compound is 0.1 to 10 moles, the amount of organic phosphorus compound is 0.1 to 10 moles, the amount of organic solvent is 0.5 to 40 moles, the amount of titanium compound is 0.5 to 25 moles, the amount of precipitation aid is 0.01 to 1 mole, and the amount of internal electron donor compound is 0.01 to 1 mole; preferably, the amount of organic epoxy compound is 0.4 to 4 moles, the amount of organic phosphorus compound is 0.8 to 4 moles, the amount of organic solvent is 2 to 30 moles, the amount of titanium compound is 1 to 20 moles, the amount of precipitation aid is 0.04 to 0.4 moles, and the amount of internal electron donor compound is 0.03 to 0.8 moles.

[0029] Optionally, according to the present invention, the amount of surfactant used is 0.01g to 1g per gram of magnesium compound.

[0030] Optionally, according to the present invention, the catalyst component for olefin polymerization has a spherical structure.

[0031] Optionally, according to the present invention, the content of titanium is 1 wt% to 5 wt%, the content of magnesium is 10 wt% to 30 wt%, the content of halogen is 40 wt% to 60 wt%, and the content of internal electron donor compound is 5 wt% to 20 wt%, based on the total weight of the solid components of the catalyst for olefin polymerization.

[0032] A second objective of this invention is to provide a method for preparing a spherical catalyst component corresponding to one objective, comprising the following steps:

[0033] S1. To bring magnesium compounds, organic epoxy compounds, and organic phosphorus compounds into contact in an organic solvent to form a magnesium-containing solution;

[0034] S2. In the presence of a precipitation aid and optionally a surfactant, a magnesium-containing solution is brought into contact with a titanium compound and an inert dispersion medium to form a mixture;

[0035] S3. The mixture is heated to precipitate spherical solids, which are then filtered, washed, and dried to obtain a solid catalyst component.

[0036] In this process, an internal electron donor compound is added during the heating process and / or after the precipitation of spherical solids; the internal electron donor compound is in contact with the spherical solids.

[0037] Optionally, the organic solvent of the present invention can be an aromatic hydrocarbon compound, specifically one or more of toluene, ethylbenzene, benzene, and xylene, with toluene being preferred.

[0038] In step S1 of this invention, there is no particular limitation on the contact method for forming the magnesium-containing solution; the purpose of the contact is to form a homogeneous magnesium-containing solution.

[0039] Optionally, in step S1 of the present invention, the contact conditions include: a contact temperature of 10°C to 100°C, preferably 20°C to 80°C, and a contact time of 0.05 to 10 hours, preferably 0.1 to 6 hours.

[0040] Optionally, the inert dispersion medium of the present invention can be one or more of white oil, hexane, heptane, octane, nonane, decane, dodecane, and cyclohexane, preferably one or more of white oil, hexane, and decane.

[0041] In step S2 of this invention, the contact method between the inert dispersion medium, the titanium compound, and the magnesium-containing solution can be any method. Specifically, it can be that the inert dispersion medium is contacted with the magnesium-containing solution to form a solution, and then the titanium compound is contacted with the solution to form a mixture; it can be that the titanium compound is contacted with the magnesium-containing solution to form a solution, and then the inert dispersion medium is contacted with the solution to form a mixture; it can also be that the inert dispersion medium and the titanium compound are mixed evenly and then dripped into the magnesium-containing solution, or the inert dispersion medium and the titanium compound are dripped into the magnesium-containing solution separately to form a mixture.

[0042] Optionally, in step S2 of the present invention, the contact temperature between the inert dispersion medium, the titanium compound, and the magnesium-containing solution is -35 to 60°C, preferably -20 to 40°C; the contact time is 1 minute to 10 hours, preferably 3 minutes to 7 hours.

[0043] Optionally, in step S2 of the present invention, the mixture formed exists in the form of colloid, two-phase solution, emulsion and other forms.

[0044] Optionally, in step S2 of the present invention, the preparation method further includes using one or more methods such as vibration, stirring, atomization, and shearing to promote uniform dispersion of the mixture.

[0045] Optionally, in step S3 of the present invention, the heating treatment includes: heating the mixture to 50-110°C to solidify and precipitate spherical solids to obtain a suspension, and then stirring the suspension at this temperature or a higher temperature (not higher than 130°C) for 10 minutes to 24 hours.

[0046] According to the present invention, the heating process of the mixture is not specifically limited, and any known method can be used for heating, such as slow, stepwise, rapid, or programmed heating. The specific heating method should be adjusted according to the specific formulation, contact temperature, etc. Furthermore, the inventors have discovered that, under the same conditions, different heating processes in the preparation method described in this invention will affect the particle morphology and particle size distribution of the final catalyst. Specifically, a slower heating process can obtain better particle morphology, while a faster heating rate will lead to a deterioration in particle shape. Therefore, the heating time of the mixture can be from 1 minute to 36 hours, preferably from 3 minutes to 24 hours.

[0047] According to the present invention, after the spherical solids precipitate from the mixture, the purpose of stirring the suspension at a certain temperature for 10 minutes to 24 hours is to make the crystal morphology more stable and improve the particle strength.

[0048] According to the present invention, spherical solids can be washed and dried using techniques known in the art.

[0049] In the preparation method of this invention, the surfactant can be added at any position before the heating treatment, and can be added all at once or in multiple parts. According to this invention, the surfactant can be added entirely or partially during or after the formation of the magnesium-containing solution; it can be added entirely to the inert dispersion medium, or partially to the inert dispersion medium and another part to the magnesium-containing solution.

[0050] Optionally, in the preparation method of the present invention, the temperature at which the surfactant is added is 10℃~100℃, preferably 10℃~80℃, and more preferably 10℃~60℃.

[0051] The internal electron-donating compound of the present invention can be added at any position after the start of the heating treatment in the preparation method, including adding it wholly or partially during the solidification and heating precipitation of the mixture; or adding it wholly or partially after the precipitation of the spherical solid or after the precipitation of the spherical solid and filtration and washing.

[0052] Optionally, in the preparation method of the present invention, the temperature at which the internal electron donor compound is added is 10℃ to 150℃, preferably 10℃ to 100℃.

[0053] Optionally, in the preparation method of the present invention, the contact time between the spherical solid and the internal electron donor compound is 0.05 to 8 hours, preferably 1 to 6 hours.

[0054] Optionally, in the preparation method of the present invention, the amount of organic epoxy compound used per mole of magnesium compound is 0.1 to 10 moles, the amount of organic phosphorus compound used is 0.1 to 10 moles, the amount of organic solvent used is 0.5 to 40 moles, the amount of titanium compound used is 0.5 to 25 moles, the amount of precipitation aid used is 0.01 to 1 mole, and the amount of internal electron donor compound used is 0.01 to 1 mole; preferably, the amount of organic epoxy compound used is 0.4 to 4 moles, the amount of organic phosphorus compound used is 0.8 to 4 moles, the amount of organic solvent used is 2 to 30 moles, the amount of titanium compound used is 1 to 20 moles, the amount of precipitation aid used is 0.04 to 0.4 moles, and the amount of internal electron donor compound used is 0.03 to 0.8 moles.

[0055] Optionally, in the preparation method of the present invention, the amount of surfactant used is 0.01g to 1g per gram of magnesium compound, and the amount of inert dispersion medium is 1g to 150g.

[0056] A third objective of this invention is to provide a catalyst system for olefin polymerization corresponding to the above-mentioned objective, the catalyst system comprising:

[0057] (1) Catalyst component; the catalyst component includes at least one selected from the spherical catalyst component prepared by the above preparation method or the spherical catalyst component described above;

[0058] (2) Alkyl aluminum compounds; and

[0059] (3)Optionally, external electron donor compounds.

[0060] Optionally, according to the present invention, the alkylaluminum compound has the general formula AlR'. n X" 3-n The compound shown has R' selected from hydrogen or hydrocarbon groups having 1 to 20 carbon atoms, especially alkyl, aralkyl, aryl, etc.; X" is a halogen, and n is an integer from 1 to 3.

[0061] Optionally, the alkylaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride, preferably triethylaluminum and / or triisobutylaluminum.

[0062] According to the present invention, the amount of the alkylaluminum compound can be a conventional amount in the art. Preferably, the molar ratio of aluminum in the alkylaluminum compound to titanium in the catalyst component is 5 to 5000:1, more preferably 20 to 800:1.

[0063] Optionally, according to the present invention, the external electron donor compound is an organosilicon compound with the general formula R". n' Si(OR y ) 4-n' In the formula, n' is an integer from 0 to 3, and R" is selected from one of alkyl, cycloalkyl, aryl, haloalkyl, halogen, and hydrogen atoms. y It is selected from one of alkyl, cycloalkyl, aryl and haloalkyl groups.

[0064] Optionally, the external electron donor compound is selected from at least one of trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyl tert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, methylcyclohexyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane, preferably methylcyclohexyldimethoxysilane.

[0065] According to the present invention, the amount of the external electron-donating compound is not particularly limited. Preferably, the molar ratio of the alkylaluminum compound to the external electron-donating compound is 0.1 to 500:1, more preferably 1 to 300:1, and more preferably 3 to 100:1, based on the aluminum content.

[0066] The fourth objective of this invention is to provide an application of a spherical catalyst component and catalyst system corresponding to the above objective in the field of olefin polymerization.

[0067] The olefin polymerization catalyst system of the present invention can be used for homopolymerization of olefins, and can also be used for copolymerization of multiple olefins.

[0068] The fifth objective of this invention is to provide an olefin polymerization method corresponding to the above objective, the method comprising: contacting one or more olefins with the above-described catalyst system under olefin polymerization conditions.

[0069] Optionally, at least one of the olefins is an olefin represented by the formula CH2=CHR, wherein R is hydrogen or a straight-chain or branched alkyl group of C1-C6.

[0070] Optionally, the olefin represented by the formula CH2=CHR is one or more of ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene, and 4-methyl-1-pentene.

[0071] Optionally, the olefin is propylene or a copolymer of propylene and other olefins.

[0072] According to the present invention, the polymerization of olefins is carried out according to known methods, in a liquid phase monomer or monomer in an inert solvent in a liquid phase, or in a gas phase, or by a combined polymerization process in a gas-liquid phase.

[0073] Optionally, the conditions for olefin polymerization include: a polymerization temperature of 0℃ to 150℃, preferably 60℃ to 100℃, and a polymerization reaction pressure of 0.1MPa to 10MPa, preferably 0.1MPa to 5MPa.

[0074] Compared with the prior art, the present invention has the following beneficial effects:

[0075] This invention uses (meth)acrylate / α-olefin copolymer as a surfactant. The prepared spherical catalyst component has a well-formed particle shape and excellent performance. When used for propylene polymerization, it has high polymerization activity and hydrogen regulation sensitivity. Attached Figure Description

[0076] Figure 1 Microscopic images of the components of the solid catalyst prepared in Example 1. Detailed Implementation

[0077] To make the present invention easier to understand, the present invention will be described in detail below with reference to embodiments. These embodiments are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used that do not specify the manufacturer are all commercially available conventional products.

[0078] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0079] The testing methods involved in the embodiments of this invention are as follows:

[0080] 1. Determination of titanium content in catalyst components: Colorimetric determination was performed using a UV-Vis spectrophotometer (model 722).

[0081] 2. Determination of the content of internal electron donor compounds in the catalyst components: The catalyst dry powder was decomposed by dilute acid, and the internal electron donor compounds were extracted with an extractant and determined by an Agilent 6890N gas chromatograph.

[0082] 3. The average particle size (D10, D50, D90) and particle size distribution (SPAN = (D90-D10) / D50) of the catalyst components were determined using a Masters Sizer 2000 particle size analyzer (manufactured by Malvern Instruments Ltd).

[0083] 4. The determination of polymer bulk density (BD) shall be in accordance with ASTM D1895-96 standard.

[0084] 5. The isotacticity index (II) of propylene polymer was determined by the heptane extraction method: 2 grams of dry polymer sample were placed in an extractor and extracted with boiling heptane for 6 hours. The residue was then dried to constant weight. The ratio of the polymer weight (g) to 2 (g) was the isotacticity.

[0085] 6. The melt flow index (MI) of the polymer was determined using a MI-4 melt flow index tester from GOTTFERT GmbH, Germany, in accordance with GB / T 3682.1-2018 standard.

[0086] 7. The number-average molecular weight (Mn) of the (meth)acrylate / α-olefin copolymer was determined using an Agilent 1260 room-temperature gel permeation chromatograph.

[0087] Example 1

[0088] (1) Preparation of catalyst components

[0089] In a 1L reactor that has been repeatedly purged with high-purity nitrogen, 10.8g of anhydrous magnesium chloride, 72mL of toluene, 9mL of epichlorohydrin, and 42mL of tributyl phosphate were added sequentially. The mixture was stirred at 300 rpm for 2 hours at 60°C. Then, 2.8g of phthalic anhydride was added, and the mixture was maintained at 60°C for another hour. The temperature was lowered to 40°C, and then 108mL of decane and 3g of dodecyl methacrylate / 1-octadecene copolymer (derived from 1-octadecene structural units, content 26wt%, Mn: 11000) were added. The mixture was stirred at 500 rpm for another hour. The solution was then cooled to 6°C, and 139.5mL of titanium tetrachloride was added dropwise. After the addition was complete, the mixture was maintained for another hour. The temperature was gradually increased to 80°C over 3 hours and maintained for 1 hour. After filtering the mother liquor, the solids were washed twice with 200mL of toluene to remove the filtrate. Add 160 mL toluene, 40 mL titanium tetrachloride, and 3.6 mL di-n-butyl phthalate, and treat at 85 °C for 1 hour, then remove the filtrate. Add 120 mL toluene and 80 mL titanium tetrachloride, and treat at 110 °C for 0.5 hours, then remove the filtrate. Add 120 mL toluene and 80 mL titanium tetrachloride, and treat at 110 °C for 0.5 hours, then remove the filtrate. Wash four times with 200 mL hexane, and then dry to obtain the solid catalyst component. Microscopic image as shown. Figure 1 As shown, the solid catalyst components have well-formed particles and good sphericity. Catalyst property data are shown in Table 1.

[0090] (2) Propylene polymerization

[0091] In a 5-liter high-pressure reactor, after complete purging with nitrogen, 5 mL of a triethylaluminum hexane solution (0.5 mmol / mL), 1 mL of a cyclohexylmethyldimethoxysilane (CHMMS) hexane solution (0.1 mmol / mL), 10 mL of anhydrous hexane, and 10 mg of solid catalyst were added at room temperature. The high-pressure reactor was then closed, and 4.5 L of hydrogen and 2.3 L of liquid propylene were added. The temperature was raised to 70 °C, and the polymerization reaction was carried out at 70 °C for 1 hour. After the reaction was completed, the reactor was cooled and stirring was stopped. The reaction product was discharged to obtain the olefin polymer. Catalyst polymerization data and polymer data are shown in Table 2.

[0092] Example 2

[0093] (1) Preparation of catalyst components

[0094] The solid catalyst component was prepared using the method of Example 1, except that a dodecyl methacrylate / 1-octadecene copolymer (59 wt% of 1-octadecene-derived structural units, Mn: 6500) was used instead of a dodecyl methacrylate / 1-octadecene copolymer (26 wt% of 1-octadecene-derived structural units, Mn: 11000). Catalyst properties are shown in Table 1.

[0095] (2) Propylene polymerization

[0096] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0097] Example 3

[0098] (1) Preparation of catalyst components

[0099] The solid catalyst component was prepared using the method of Example 1, except that octadecyl methacrylate / 1-dodecene copolymer (33 wt% 1-dodecene-derived structural units, Mn: 10700) was used instead of octadecyl methacrylate / 1-octadecene copolymer (26 wt% 1-octadecene-derived structural units, Mn: 11000). Catalyst properties are shown in Table 1.

[0100] (2) Propylene polymerization

[0101] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0102] Example 4

[0103] (1) Preparation of catalyst components

[0104] The solid catalyst component was prepared using the method of Example 1, except that octadecyl methacrylate / 1-octadecene copolymer (40 wt% 1-octadecene-derived structural units, Mn: 4200) was used instead of dodecyl methacrylate / 1-octadecene copolymer (26 wt% 1-octadecene-derived structural units, Mn: 11000). Catalyst properties are shown in Table 1.

[0105] (2) Propylene polymerization

[0106] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0107] Example 5

[0108] (1) Preparation of catalyst components

[0109] The solid catalyst component was prepared using the method of Example 1, except that dodecyl methacrylate / 1-hexadecene copolymer (38 wt% of 1-hexadecene-derived structural units, Mn: 13900) was used instead of dodecyl methacrylate / 1-octadecene copolymer (26 wt% of 1-octadecene-derived structural units, Mn: 11000). Catalyst properties are shown in Table 1.

[0110] (2) Propylene polymerization

[0111] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0112] Example 6

[0113] (1) Preparation of catalyst components

[0114] The solid catalyst component was prepared using the method of Example 1, except that 2-ethylhexyl methacrylate / 1-tetradecene copolymer (47 wt% of 1-dodecene-derived structural units, Mn: 26000) was used instead of dodecyl methacrylate / 1-octadecene copolymer (26 wt% of 1-octadecene-derived structural units, Mn: 11000). Catalyst properties are shown in Table 1.

[0115] (2) Propylene polymerization

[0116] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0117] Example 7

[0118] (1) Preparation of catalyst components

[0119] In a 1L reactor that has been repeatedly purged with high-purity nitrogen, 10.8g of anhydrous magnesium chloride, 72mL of toluene, 9mL of epichlorohydrin, and 42mL of tributyl phosphate were added sequentially. The mixture was stirred at 300 rpm for 2 hours at 60°C. Then, 2.8g of phthalic anhydride was added, and the mixture was kept at 60°C for another hour. The temperature was lowered to 40°C, and then 108mL of decane and 3g of dodecyl methacrylate / 1-octadecene copolymer (59wt% of 1-octadecene structural units, Mn: 6500) were added. The mixture was stirred at 500 rpm for another hour. The solution was then cooled to 6°C, and 139.5mL of titanium tetrachloride was added dropwise. After the addition was complete, the temperature was maintained for another hour. The temperature was gradually increased to 80°C over 3 hours and maintained for 1 hour. During the heating process, 3mL of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane was added. After filtering the mother liquor, the solids were washed twice with 200mL of toluene. Add 120 mL toluene and 80 mL titanium tetrachloride, treat at 110 °C for 0.5 hours, and remove the filtrate. Wash four times with 200 mL hexane, and then dry to obtain the solid catalyst component. Catalyst properties are shown in Table 1.

[0120] (2) Propylene polymerization

[0121] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0122] Example 8

[0123] (1) Preparation of catalyst components

[0124] The solid catalyst component was prepared using the method of Example 7, except that dodecyl methacrylate / 1-hexadecene copolymer (38 wt% of 1-hexadecene-derived structural units, Mn: 13900) was used instead of dodecyl methacrylate / 1-octadecene copolymer (59 wt% of 1-octadecene-derived structural units, Mn: 6500). Catalyst properties are shown in Table 1.

[0125] (2) Propylene polymerization

[0126] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0127] Comparative Example 1

[0128] (1) Preparation of catalyst components

[0129] The solid catalyst component was prepared using the method of Example 1, except that the dodecyl methacrylate / 1-octadecene copolymer (derived from 26 wt% 1-octadecene structural units, Mn: 11000) was used instead of the surfactant T602 (poly(meth)acrylate polymer). Catalyst properties are shown in Table 1.

[0130] (2) Propylene polymerization

[0131] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0132] Comparative Example 2

[0133] (1) Preparation of catalyst components

[0134] The solid catalyst component was prepared using the method of Example 1, except that the surfactant T632 (an alcoholysis product of maleic anhydride / methacrylate copolymer) was used instead of the dodecyl methacrylate / 1-octadecene copolymer (26 wt% of 1-octadecene-derived structural units, Mn: 11000). Catalyst properties are shown in Table 1.

[0135] (2) Propylene polymerization

[0136] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0137] Comparative Example 3

[0138] (1) Preparation of catalyst components

[0139] The solid catalyst component was prepared using the method of Example 7, except that T632 (an alcoholysis product of maleic anhydride / methacrylate copolymer) was used instead of dodecyl methacrylate / 1-octadecene copolymer (59 wt% of 1-octadecene-derived structural units, Mn: 6500). Catalyst properties are shown in Table 1.

[0140] (2) Propylene polymerization

[0141] The polymerization conditions were the same as in Example 1, and the polymerization data and polymer data are shown in Table 2.

[0142] Table 1.

[0143]

[0144] Table 2.

[0145]

[0146]

[0147] As can be seen from the above embodiments and comparative examples, in the preparation method of the present invention, when using the same internal electron donor compound, the catalyst component prepared by using (meth)acrylate / α-olefin copolymer as a surfactant not only has good sphericity but also excellent catalyst performance. When used for propylene polymerization, the catalyst exhibits high activity, especially at high hydrogen concentrations, resulting in a higher melt index of the polymer.

[0148] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.

Claims

1. A spherical catalyst component, characterized in that, The reaction products contain the following components or the following components: (1) magnesium compounds; (2) organic epoxy compounds; (3) organophosphorus compounds; (4) precipitation aids; (5) titanium compounds; (6) internal electron donor compounds; (7) surfactants; The surfactant is a (meth)acrylate / α-olefin copolymer; The (meth)acrylate monomer in the (meth)acrylate / α-olefin copolymer is derived from the general formula CH2=C(R) a COO(R) b ) indicates that R a R is a hydrogen atom or a methyl group. b Selected from straight-chain or branched alkyl groups with 1 to 30 carbon atoms, cycloalkyl groups with 3 to 30 carbon atoms, or aromatic groups with 6 to 30 carbon atoms; The α-olefin monomer in the (meth)acrylate / α-olefin copolymer is derived from the general formula CH2=CHR. c It means that R c Selected from hydrogen atoms, straight-chain or branched alkyl groups with 1 to 30 carbon atoms, and cycloalkyl groups with 3 to 30 carbon atoms; The content of α-olefin-derived structural units in the (meth)acrylate / α-olefin copolymer is 10wt%~90wt%.

2. The spherical catalyst component according to claim 1, characterized in that, The content of α-olefin-derived structural units in the (meth)acrylate / α-olefin copolymer is 20wt%~80wt%.

3. The spherical catalyst component according to claim 1, characterized in that, The (meth)acrylate monomer is selected from one or more of the following: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, tetradecyl methacrylate, hexadecyl methacrylate, octadecyl methacrylate, eicosyl methacrylate, and dodecyl methacrylate. And / or, the α-olefin monomer is selected from one or more of 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetracene, 1-tetradecene, 1-pentadene, 1-hexadecene, 1-heptadecene, 1-heptadecene, 1-octadecene, 1-nonadene, 1-eicosene, 1-docosahexadecene, 1-hexadecene, 3-methyl-1-butene, and 4-methyl-1-pentene.

4. The spherical catalyst component according to claim 1, characterized in that, The magnesium compound has the general formula MgX2, wherein X is selected from bromine, chlorine or iodine; And / or, the organic epoxy compound is selected from one or more of the oxidation products of aliphatic olefins and the oxidation products of halogenated aliphatic olefins. And / or, the organophosphorus compound is selected from one or more compounds of formula (1) and formula (2); Equation (1) Equation (2) In formulas (1) and (2), R1, R2, R3, R4, R5 and R6 are each independently selected from straight-chain or branched alkanes with 1 to 20 carbon atoms, cycloalkanes with 1 to 20 carbon atoms, haloalkanes with 1 to 20 carbon atoms, aromatic hydrocarbons with 1 to 20 carbon atoms or aromatic hydrocarbons with substituents with 1 to 20 carbon atoms. And / or, the precipitation aid is selected from one or more of organic acid anhydrides, organic acids, organic ketones, and organic ethers; And / or, the titanium compound is composed of the structural formula TiX' m (OR d ) 4-m This indicates that X' is a halogen and R d A hydrocarbon group consisting of 1 to 20 carbon atoms, where m is an integer from 1 to 4; And / or, the internal electron donor compound is selected from one or more of esters, ethers, ketones, amines, and silanes.

5. The spherical catalyst component according to claim 4, characterized in that, The organic epoxy compound is selected from one or more of ethylene oxide, propylene oxide, epichlorohydrin, epichlorohydrin, butane oxide, butadiene oxide, butadiene dioxide, methyl glycidyl ether, and diglycidyl ether. And / or, the organophosphorus compound is selected from one or more of trimethyl phosphate, triethyl phosphate, tributyl phosphate, tripentyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, and benzyl phosphite; And / or, the precipitation aid is selected from one or more of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic dianhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, dimethyl ether, diethyl ether, propyl ether, butyl ether, and pentyl ether. And / or, the titanium compound is selected from one or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxy, titanium tetraethoxy, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloromonoethoxy. And / or, the internal electron-donating compound is selected from one or more of mono- or poly-aliphatic carboxylic acid esters, aromatic carboxylic acid esters, diol esters, and diethers, more preferably from one or more of phthalates, malonates, succinates, glutarates, and 1,3-diethers.

6. The spherical catalyst component according to claim 5, characterized in that, The internal electron donor compound is selected from one or more of di-n-butyl phthalate, diisobutyl phthalate, 2,4-pentanediol dibenzoate, 3,5-heptanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, diisobutyl 2,2-dimethylsuccinate, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-dimethoxymethylfluorene.

7. The spherical catalyst component according to any one of claims 1-6, characterized in that, The spherical catalyst component also includes an organic solvent; the organic solvent is an aromatic hydrocarbon compound.

8. The spherical catalyst component according to claim 7, characterized in that, The organic solvent is one or more of toluene, ethylbenzene, benzene, and xylene.

9. The spherical catalyst component according to any one of claims 1-6, characterized in that, For every mole of magnesium compound, the amount of organic epoxy compound is 0.1 to 10 moles, the amount of organic phosphorus compound is 0.1 to 10 moles, the amount of organic solvent is 0.5 to 40 moles, the amount of titanium compound is 0.5 to 25 moles, the amount of precipitation aid is 0.01 to 1 mole, and the amount of internal electron donor compound is 0.01 to 1 mole. And / or, the amount of surfactant used is 0.01g to 1g per gram of magnesium compound; And / or, based on the total weight of the spherical catalyst component, the content of titanium is 1wt%~5wt%, the content of magnesium is 10wt%~30wt%, the content of halogen is 40wt%~60wt%, and the content of internal electron donor compound is 5wt%~20wt%; And / or, the number average molecular weight of the (meth)acrylate / α-olefin copolymer is 1,000 to 100,000.

10. The spherical catalyst component according to claim 9, characterized in that, For every mole of magnesium compound, the amount of organic epoxy compound is 0.4 to 4 moles, the amount of organic phosphorus compound is 0.8 to 4 moles, the amount of organic solvent is 2 to 30 moles, the amount of titanium compound is 1 to 20 moles, the amount of precipitation aid is 0.04 to 0.4 moles, and the amount of internal electron donor compound is 0.03 to 0.8 moles.

11. A method for preparing a spherical catalyst component according to any one of claims 1 to 10, characterized in that, Includes the following steps: S1. To bring magnesium compounds, organic epoxy compounds, and organic phosphorus compounds into contact in an organic solvent to form a magnesium-containing solution; S2. In the presence of a precipitation aid and optionally a surfactant, a magnesium-containing solution is contacted with a titanium compound and an inert dispersion medium to form a mixture; S3. The mixture is heated to precipitate spherical solids, which are then filtered, washed, and dried to obtain a solid catalyst component; In this process, an internal electron donor compound is added during the heating process and / or after the precipitation of spherical solids, and the internal electron donor compound comes into contact with the spherical solids.

12. The preparation method according to claim 11, characterized in that, In step S1, the contact conditions include: a contact temperature of 10℃ to 100℃ and a contact time of 0.05 to 10 hours. And / or, in step S2, the inert dispersion medium is selected from one or more of white oil, hexane, heptane, octane, nonane, decane, dodecane, and cyclohexane; And / or, in step S2, the contact conditions include: a contact temperature of -35 to 60°C; and a contact time of 1 minute to 10 hours. And / or, in step S2, the mixture exists in the form of a colloid, a two-phase solution, or an emulsion; And / or, in step S2, the temperature at which the surfactant is added is 10℃~100℃; And / or, in step S3, the heating treatment includes: heating the mixture to 50~110℃, solidifying and precipitating spherical solids to obtain a suspension, the heating time being 1 minute to 36 hours, and then stirring the suspension at 50~130℃ for 10 minutes to 24 hours; And / or, in step S3, the temperature at which the internal electron-donating compound is added is 10°C to 150°C; And / or, in step S3, the contact time between the spherical solid and the internal electron donor compound is 0.05 to 8 hours.

13. The preparation method according to claim 12, characterized in that, In step S1, the contact conditions include: a contact temperature of 20°C to 80°C and a contact time of 0.1 to 6 hours. And / or, in step S2, the contact conditions include: a contact temperature of -20 to 40°C; and a contact time of 3 minutes to 7 hours. And / or, in step S2, the temperature at which the surfactant is added is 10℃~60℃; And / or, in step S3, the temperature at which the internal electron-donating compound is added is 10°C to 100°C; And / or, in step S3, the contact time between the spherical solid and the internal electron-donating compound is 1 to 6 hours.

14. The preparation method according to any one of claims 11-13, characterized in that, In the preparation method, the amount of organic epoxy compound used per mole of magnesium compound is 0.1-10 moles, the amount of organic phosphorus compound used is 0.1-10 moles, the amount of organic solvent used is 0.5-40 moles, the amount of titanium compound used is 0.5-25 moles, the amount of precipitation aid used is 0.01-1 mole, and the amount of internal electron donor compound used is 0.01-1 mole. And / or, in the preparation method, the amount of surfactant used is 0.01g to 1g per gram of magnesium compound, and the amount of inert dispersion medium is 1g to 150g.

15. The preparation method according to claim 14, characterized in that, In the preparation method, per mole of magnesium compound, the amount of organic epoxy compound is 0.4-4 moles, the amount of organic phosphorus compound is 0.8-4 moles, the amount of organic solvent is 2-30 moles, the amount of titanium compound is 1-20 moles, the amount of precipitation aid is 0.04-0.4 moles, and the amount of internal electron donor compound is 0.03-0.8 moles.

16. A catalyst system, characterized in that, The catalyst system includes: (1) Catalyst component; the catalyst component includes at least one selected from the spherical catalyst component according to any one of claims 1 to 10 and the spherical catalyst component prepared by the preparation method according to any one of claims 11 to 15; (2) Alkyl aluminum compounds; and (3)Optionally, external electron donor compounds.

17. The catalyst system according to claim 16, characterized in that, The alkylaluminum compound has the general formula AlR' n X" 3-n The compound shown is in which R' is a hydrocarbon group with 1 to 20 hydrogen atoms, X" is a halogen, and n is an integer from 1 to 3; And / or, the molar ratio of aluminum in the alkylaluminum compound to titanium in the catalyst component is 5~5000:1; And / or, the external electron donor compound is an organosilicon compound with the general formula R". n' Si(OR y ) 4-n' Where n' is an integer from 0 to 3, and R" is selected from one of alkyl, cycloalkyl, aryl, halogenated alkyl, halogen, and hydrogen atoms. y Selected from one of alkyl, cycloalkyl, aryl, and halogenated alkyl groups; And / or, based on the aluminum content, the molar ratio of the alkylaluminum compound to the external electron donor compound is 0.1 to 500:

1.

18. The catalyst system according to claim 17, characterized in that, In the general formula AlR' n X" 3-n In this context, R' represents alkyl, aralkyl, or aryl. And / or, the molar ratio of aluminum in the alkylaluminum compound to titanium in the catalyst component is 20~800:1; The external electron donor compound is selected from at least one of trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyl tert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, methylcyclohexyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane. And / or, based on the aluminum content, the molar ratio of the alkylaluminum compound to the external electron donor compound is 3~100:

1.

19. The catalyst system according to claim 18, characterized in that, The alkylaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride.

20. The application of a spherical catalyst component according to any one of claims 1 to 10, a spherical catalyst component prepared by any one of claims 11 to 15, or a catalyst system according to any one of claims 16 to 19 in olefin polymerization reactions.

21. A method for olefin polymerization, characterized in that, The method includes contacting one or more olefins with the catalyst system according to any one of claims 16 to 19 under olefin polymerization conditions.

22. The method according to claim 21, characterized in that, At least one of the olefins is an olefin represented by the formula CH2=CHR, wherein R is hydrogen or a straight-chain or branched alkyl group of C1-C6. And / or, the conditions for olefin polymerization include: polymerization temperature of 0℃ to 150℃ and polymerization reaction pressure of 0.1MPa to 10MPa.

23. The method according to claim 22, characterized in that, The olefin represented by the formula CH2=CHR is one or more of ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene, and 4-methyl-1-pentene; And / or, the conditions for olefin polymerization include: polymerization temperature of 60℃~100℃ and polymerization reaction pressure of 0.1MPa~5MPa.

Citation Information

Patent Citations

  • Emulsion method for improving large spherical polypropylene catalysts

    CN103619475B

  • Process for preparing spherical polymerization catalyst components for use in olefin polymerizations

    CN107207657A

  • Catalyst for polymerization or copolymerization of propylene and its preparation and application

    CN1097597C

  • Preparation method of olefin polymerization catalyst component and prepared olefin polymerization catalyst component

    CN114426597A

  • Catalyst system used for alkene poly-and copolymerization

    CN85100997A